(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
The analysis of protection and rescue in Denmark, in terms of transnational dynamics and the compatibility or non-compliance of civil defense with the concepts of statehood, citizenship, or national goal - provides a comparison of the development of national civil defense in the West during the Cold War. Protection and rescue in Denmark is an example of the evolution of the civil defense system. The author tries to point out the functionality through the idea, construction, compliance, legal support but also the available critiques of the protection and rescue system. The reflections are on the timeliness of the conception, the legitimacy, and the presentation to the public of civil defense. Questions are asked about the success of the training methods for the professional staff and volunteers as well as the teaching to the general public; for the reproduction and materialization of political and cultural narratives of prosperity and war; for post-war urban planning; and for shelters as material and psychological support. The available data indicate that the continuous development of civil defense in Denmark in the Cold War and civil protection in the decades after it results in a system that is an example of the conceptual, structural, and functional setup of a modern and effective protection and rescue system.